1903 S.C. Acts 124, no. 82, § 1. - (:unkn) unknown (My University, 1903)
Be it enacted by the General Assembly of the State of South Carolina, That no person shall sell, deliver or dispose of dynamite or similar powerful explosives, except ordinary gunpowder, unless such person knows the purchaser or the party to receive the same and is satisfied that the explosive is not to be used for killing fish, and then only upon a written application from party desiring to purchase, stating the purpose for which he desires to use the said explosives; and a person selling, delivering or disposing of such explosives, shall keep a book in which shall be recorded the name of the purchaser or party to whom the explosive is delivered, the quantity so sold or delivered, and the date of such sale or delivery.
Keywords: FISHING REGULATION; TRANSFER, MANUFACTURE & POSSESSION - TOYS AND EXPLOSIVES